2007
DOI: 10.1375/anft.28.2.61
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Child Therapy (PACT) In Action: An Attachment‐Based Intervention for a Six‐Year‐Old With a Dual Diagnosis

Abstract: This case study explores Parent and Child Therapy (PACT), an attachment‐based intervention for mothers and children experiencing intractable relationship distress originally developed by Heather Chambers (a Child Psychotherapist and Family Therapist working in New Zealand). We describe the use of PACT with a mother—child dyad presenting a history of severe abuse and neglect. The child had been diagnosed with Conduct Disorder and co‐morbid Attention Deficit Hyperactivity Disorder. We consider the themes arising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…For example, the Childhaven's Childhood Trauma Treatment is based on a model of therapeutic childcare, which recommends children aged 0-5 years attend 5.5 hours of treatment, 5 days per week for a duration that is individually determined (depending on the circumstances of each child) (Armsden et al, 1998). This example and others (Amos et al, 2007) illustrate the need for ambulatory mental health services to be able to offer intensive and long-term therapy, through multidisciplinary teams and with a capacity to respond flexibly to the complex needs of highly vulnerable children and families, typical of those with mental health concerns.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Childhaven's Childhood Trauma Treatment is based on a model of therapeutic childcare, which recommends children aged 0-5 years attend 5.5 hours of treatment, 5 days per week for a duration that is individually determined (depending on the circumstances of each child) (Armsden et al, 1998). This example and others (Amos et al, 2007) illustrate the need for ambulatory mental health services to be able to offer intensive and long-term therapy, through multidisciplinary teams and with a capacity to respond flexibly to the complex needs of highly vulnerable children and families, typical of those with mental health concerns.…”
Section: Discussionmentioning
confidence: 99%
“…After construction, the model was used to predict the fundamental objectives of any effective treatment for these families. The model and these objectives are briefly described below, to provide a context for the second part of the manuscript, where the authors analyse, in the light of the proposed theory, the unique use of the one-way screen in the dyadic psychotherapeutic protocol, Parallel Parent and Child Therapy ( 10 , 11 ). The purpose of this analysis was primarily to propose a mechanism of action of the one-way screen, identified as an instrumental element of the therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In response to these difficulties we have been experimenting with an intensive relationship-focused dyadic psychotherapy called parallel parent child narrative/parent and child therapy (PPCN/PACT; Amos, Beal, & Furber, 2007;Chambers, Amos, Allison, & Roeger, 2006). We have found that children who failed to improve with other interventions respond well to this relational approach.…”
Section: Introductionmentioning
confidence: 99%